Doing Memory and Contentious Participation : Remembering the Victims of Right-Wing Violence in German Political Culture - Steffen Rudolph; Tanja Thomas; Fabian Virchow (2019)
Doing Memory and Contentious Participation: Remembering the Victims of Right-Wing Violence in German Political Culture by Steffen Rudolph, Tanja Thomas, and Fabian Virchow discusses the relevance of remembering as part of political culture and as a potential way of contentious participation around issues of belonging and recognition. The chapter uses the case of contested memory with regard to the deadly arson attack against migrants in Mölln as a case study and argues that forms of collaboration between the victims of right-wing violence and activists vitally rely on the use of digital media to foster solidary bonds and connections. By addressing resource-based hierarchies as well as by listening to the voices of the victims and the marginalized, this collaboration is quintessential for shaping the future of a post-migrant society that is aware of racist violence.
Keywords: Right-wing Violence; Memory Culture; Post-war Germany; Political Science; Doing Memory; Media Studies